Effect of Operational Risk on Financial Performance in Banking Industry IDX - Ery Santika; Muhammad Hadyan Fakhrughozy; Wahyu Muhammad Nur; Henny Setyo Lestari (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
Seeing the phenomenon of the COVID-19 pandemic, it has resulted in changes in the work patterns of many banks in Indonesia. The presence of COVID 19 is able to change the current pattern of bank operations in Indonesia. The financial performance of a company is a measure of the company's profits or losses in a certain period of time. Which could be issues related to banking risk management such as exchange rate risk, operational risk and interest rate risk. To raise arguments about how risk affects financial performance can reduce the probability of bankruptcy and provide greater stability of banking. This study aims to determine the effect of the dependent variable on financial performance as measured by return on assets and return on equity and the independent variable net interest income, average asset turnover, total operating expense, interest over years, exchange rate. The purpose of this study is to examine the effect of operational risk on financial performance in the banking industry listed on the IDX.